Synthesis, Spectral and Thermal Characterization of The Complexes of Palladium(II), Platinum(II) and Mercury(II) with 2-Thioquinaldine Anilide - Jha, Yogendra (Asian Journal of Chemistry, 2010)
The complexes of palladium(II), platinum(II) and mercury(II) with 2-thio quinaldine anilide have been prepared and characterized by elemental analysis, magnetic and electronic spectral studies. The studies suggest square planner geometry to all the palladium(II) and platinum(II) complexes and tetrahedral geometry to the mercury(II) complexes with ligand in which nitrogen and sulphur are as donor atoms.